Pengaruh Kemampuan Komunikasi dan Kualitas SDM Aparat Pemerintah Desa Terhadap Pembangunan Desa: (Studi pada Desa Se-Kecamatan Purwaharja Kota Banjar) - Lusy Suciati; Enas Enas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is motivated by the low communication skills, the slow development process in villages throughout Purwaharja District is thought to be caused by the low skills of village officials throughout Purwaharja District. The ability here is seen from their daily performance which is sometimes unable to keep up with the demands of technological progress, or is also caused by their low level of education and work experience. The purpose of this study is to determine how communication skills affect village development, how the quality of village government officials' human resources affects village development, and how communication skills and the quality of village government officials' human resources together affect village development. The method used in this study uses a quantitative descriptive method. To analyze it, correlation and multiple regression statistical test data analysis was used using SPSS version 22.00. The results of the study obtained provide the conclusion that communication skills have a positive effect on village development, the quality of village government officials' human resources have a positive and significant effect on village development, and communication skills and the quality of village government officials' human resources together have a positive effect on village development.